Pembiasaan Tadarus Al-Qur’an Dalam Projek Penguatan Profil Pelajar Pancasila Di SMP N 3 Kertek Wonosobo - Rina Fitrohati; Abdul Majid; Fatiatun (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
The moral decadence that occurred at SMP N 3 Kertek Wonosobo after the pandemic, which was exacerbated by learning loss in students, made the school finally make the habit of Al-Qur'an recitation as a program in the project to strengthen the Pancasila student profile, especially for Dimension I, namely faith, fear of God Almighty, and noble character. This research aims to find out the concept, effectiveness and obstacles and support in the program. The type of research used is field qualitative with a qualitative descriptive approach. Data were collected using non-participant observation, free guided interviews and documentation. The data was analyzed by reducing, presenting the data and then drawing conclusions. The results showed that the concept of strengthening the first dimension of the Pancasila student profile through the Al-Qur'an recitation habituation program was integrated in the process of implementing the program starting from the preparation stage to the assessment stage. The program has not been effective in improving the morals of students. The supporting factors and inhibiting factors in the program come from internal and external factors, respectively.